Avanços e desafios das políticas públicas de formação de professores das escolas do campo na Paraíba - Silva, Josiane Ferreira de Lima (2015)
This study aimed to analyze and understand the advances and challenges of public policies for teachers training of Basic Education to the schools of the field in Paraíba, in the last four years (2011-2014). The research is justified primarily by the fact that it dwells on an educational theme which has a historic deficit and is extremely challenging for the governments (at all federal levels) and universities, this is, the training of teachers to the schools of the field throughout the country. The methodology used to better understand the object of study was a qualitative research, based on authors such as Mello (2005) and Triviños (1987) with their studies on research methodologies. The theoretical foundation was made starting from the conceptions of authors that address teachers training as an essential factor in building a quality education, including: Freire (1992; 1996; 2005), Arroyo (2005; 2007), Caldart (2004) Freitas (2011) and others. For a better understanding of the object of study searching to answer and reach the objectives outlined, it was made a mapping of the actions of public universities in the state, UFPB and UFCG, and the exploratory analysis of one of the state government's actions which was the Course of Specialization in Educational Background: Interdisciplinary Pedagogical Practices. The results found, through the research, pointed out that public policies for teachers training of basic education of the field in the state are not consolidated; they indicates that there are courses offered by public universities, UFCG with a Degree in Education of the Field and UFPB with Pronera courses. Therefore, the study showed that, despite the advances are few, in relation to the demand and the need, the public universities still are the institutions that most contribute to the training of teachers to this specificity.